PENGEMBANGAN MULTIMEDIA PEMBELAJARAN BERBASIS WEBSITE PADA MATA PELAJARAN SOSIOLOGI SISWA KELAS X MADRASAH ALIYAH NEGERI 1 BATANG HARI MEMBENTUK KETELADANAN DALAM PERILAKU - Djong, Fahri Firdaus; M. Rusdi; Hary Soedarto Sarjono (MAN Insan Cendekia Jambi, 2021)
ABSTRACT This research aims to know: (1) The process of multimedia development of website-based learning on the subjects of Sociology, (2) information on the feasibility of multimedia products based learning website on the subjects of sociology grade X class Madrasah AliyahThis method of research is Research and Development (R&D) with the development method of ADDIE (Analysis, Design, Development, Implementation, Evaluation). The research was located at MAN 1 Batang Hari in March 2020. Data collection instruments are observations and polls. This multimedia learning feasibility is assessed by a team of learning design experts, website design experts, material experts and practitioners.The results explained that: (1) Multimedia based website learning has been developed with the address http://digsostory.com. (2) Multimedia-based learning website on the subject of sociology of class X Madrasah Aliyah Negeri 1 Batang Hari deserves to be used as a learning media after the interview and validation by experts and practitioners. Keywords: multimedia learning, the subjects of the sociology, website-based learning, Research and Development